2004
DOI: 10.1111/j.1048-891x.2004.14529.x
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor, progesterone receptor, and bcl-2 are markers with prognostic significance in CIN III

Abstract: Abstract. Fonseca-Moutinho JA, Cruz E, Carvalho L, Prazeres HJM, de Lacerda MMP, da Silva DP, Mota F, de Oliveira CF. Estrogen receptor, progesterone receptor, and bcl-2 are markers with prognostic significance in CIN III. Int J Gynecol Cancer 2004;14:911-920.There are no known biological markers or technologies to predict the natural history of an individual CIN III. The probability of progression is considered greater with the persistence of high-risk human papillomavirus (HPV) infection and age. p53 polymor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 82 publications
2
9
0
Order By: Relevance
“…These data confirm the observations of Fonseca-Moutinho et al, (2004), that Bcl2 is an independent factor in defining low risk of progression for CIN 3 and co-expression of estrogen receptor, progesterone receptor, and Bcl2 may be a useful tool in identifying the CIN 3 lesions with low risk of progression toward cervical cancer. Bcl2 has a more important value in cancer, the ratio of Bcl2 to Bax expression determining the survival or the death following an apoptotic stimulus.…”
Section: Wwwintechopencomsupporting
confidence: 90%
“…These data confirm the observations of Fonseca-Moutinho et al, (2004), that Bcl2 is an independent factor in defining low risk of progression for CIN 3 and co-expression of estrogen receptor, progesterone receptor, and Bcl2 may be a useful tool in identifying the CIN 3 lesions with low risk of progression toward cervical cancer. Bcl2 has a more important value in cancer, the ratio of Bcl2 to Bax expression determining the survival or the death following an apoptotic stimulus.…”
Section: Wwwintechopencomsupporting
confidence: 90%
“…Increased Bcl-2 protein expression appears to be associated with cervical carcinogenesis [40] . In several studies, Bcl-2 expression was increased in early [32,41] as well as advanced stages [8,42] of cervical lesions. In our study, Bcl-2 expression gradually increased from LSIL to HSIL with a statistical significance ( table 2 ), suggesting an association between Bcl-2 expression with stages of cervical dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…In the same way, Spinillo et al (2004) showed an increase of Bcl-2 expression correlated with the severity of CIN. Fonseca-Moutinho et al (2004) observed that estrogen receptor (ER) and progesterone receptor (PR), Bcl-2, and Bax immunohistochemical expression was stronger and more frequent in the CIN III group. After a multivariable analysis, coexpression of ER, PR, and Bcl-2 was the only independent factor in defining low risk of progression for CIN III.…”
Section: Discussionmentioning
confidence: 98%